IL-1R1 is expressed on both Helios+ and Helios−FoxP3+CD4+ T cells in the rheumatic joint. (30th July 2015) - Müller, M; Herrath, J; Malmström, V
Summary: Synovial fluid from rheumatic joints displays a well-documented enrichment of forkhead box protein 3 (FoxP3) + regulatory T cells (tissue Tregs ). However, we have previously demonstrated that the mere frequency of FoxP3 expressing cells cannot predict suppressive function. Instead, extrinsic factors and the functional heterogeneity of FoxP3 + Tregs complicate the picture. Here, we investigated FoxP3 + Tregs from blood and synovial fluid of patients with rheumatic disease in relation to Helios expression by assessing phenotypes, proliferative potential and cytokine production by flow cytometry. Our aim was to investigate the discriminatory potential of Helios when studying FoxP3 + Tregs in an inflammatory setting. We demonstrate that the majority of the synovial FoxP3 + CD4 + T cells in patients with inflammatory arthritis expressed Helios. Helios + FoxP3 + Tregs displayed a classical Treg phenotype with regard to CD25 and cytotoxic T lymphocyte-associated antigen (CTLA)-4 expression and a demethylated Treg -specific demethylated region (TSDR). Furthermore, Helios + FoxP3 + T cells were poor producers of the effector cytokines interferon (IFN)-γ and tumour necrosis factor (TNF), as well as of the anti-inflammatory cytokine interleukin (IL)-10. The less abundant Helios – FoxP3 + T cell subset was also enriched significantly in the joint, displayed a overlapping phenotype to the double-positive Treg cells with regard to CTLA-4 expression, but differed by their ability to secrete IL-10, IFN-γ and TNF upon T cell receptor (TCR) cross-linking. We also demonstrate a striking enrichment of IL-1R1 expression in synovial CD4 + T cells that was restricted to the CD25-expressing FoxP3 population, but independent of Helios. IL-1R1 expression appears to define a tissue Treg cell phenotype together with the expression of CD25, glucocorticoid-induced TNF receptor family-related gene (GITR) and CTLA-4.